How to Teach The Suprasegmentals of English To Farsi-speakers Learning English as a Foreign Language - mohammad poursina (Matn/Pizhūhī-i Adabī, 2000)
The major objective of the present writer is to survey some of the problems that Iranian learners of English encounter as to the use of English stress patterns and Intonation. It seems rather obvious that the main source of difficulty in the use of English stress and intonation is the interference comingfrom the learners' mother tongue, i.e. Persian. The present writer also tries to offer some solutions to the fundamental problems of Iranian learners of English in the area of stress and Intonation.